T The Constant of Kp and Kow of Phthalates in Indoor Air in Vietnam - Hanh, Le Thi; Minh, Tu Binh; Tri, Tran Minh (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2, 2018)
Several previous studies, phthalates have been reported to be reproductive and endocrine toxicants in laboratory animals. However, the wide use of phthalates is the cause of common distribution of these compounds in various environments such as air, dust, wastewater, and food, etc., and their metabolism forms have been found in human blood and urine. In which, the distribution coefficients of phthalates and volatile compound in indoor air is attracting a lot of attention. This report mentions the distribution coefficients of ten phthalates between vapor phase and particle phase from indoor airin some cities in Vietnam. The gas-particle partition coefficient (Kp) and the octanol-water partition coefficient (Kow) of phthalates were calculated on the basis of the measured concentration in vapor phase and particulate phases. The meanlogKp valuesof ten phthalates ranged from -2.16 to -1.31, meanwhile the mean logKow values ranged from 10.23 to 11.08. It is the difference of the logKp and logKow values between standard and real indoor air conditions. These results suggest that the Kp and Kow values of phthalates are strongly depend on the environmental conditions. Keywords Phthalates, Kp, Kow, indoor air References 1. A. Finizio, A. Mackay, T. Bidleman, T. Harner, Octanol-air partition coefficient as a predictor of partitioning of semi-volatile organic chemicals to aerosols. Atmos. Environ. 31 (1997) 2289-2296. 2. C.J. Weschler, G. Beko, H.M. Koch, T. Salthammer, T. Schripp, J. Toftum, et al., Transdermal uptake of diethyl phthalate and di(n-butyl) phthalate directly from air: experimental verification, Environ. Health Perspect. 123 (2015) 928-934. 3. C.J. Weschler, W.W. Nazaroff, SVOC partitioning between the gas phase and settled dust indoors. Atmos. Environ. 44 (2010) 3609-3620. 4. G. Bekö, C.J. Weschler, S. Langer, M. Callesen, J. Tofrum, G. Clausen, Chilren's phthalate intakes and resultant cumulative exposures estimated from urine compared with estimates from dust ingestion, inhalation and dermal absorption in their homes and daycare centers, PLoS One 8, e6 (2013) 24-42. 5. G.C. Morrison, C.J. Weschler, G. Beko, H.M. Koch, T. Salthammer, T. Schripp, et al., Role of clothing in both accelerating and impeding dermal absorption of airborne SVOCs, J. Expo. Sci. Environ. Epidemiol. 26 (2016) 113-118. 6. H. Q. Anh, L. M. Thùy, T. B. Minh, K. Kannan, T. M. Trí. Sự phân bố đieste phtalat trong bụi trong nhà tại một số tỉnh thành phía Bắc Việt Nam. Tạp chí Hóa học, 53 (6e1,2) (2015) 287-290. 7. H.M. Stapleton, S.M. Kelly, J.G. Allen, M.D. McClean, T.F. Webster, Measurement of polybrominated diphenyl ethers on hand wipes: estimating exposure from hand-tomouth contact, Environ. Sci. Technol. 42 (2008) 3329-3334. 8. M. Abb, T. Heinrich, E. Sorkau, W. Lorenz, Phthalates in house dust, Environ. Int. 35 (2009) 965-970. 9. M. Gong, C.J. Weschler, Y. Zhang, Impact of clothing on dermal exposure to phthalates: observations and insights from sampling both skin and clothing, Environ. Sci. Technol. 50 (2016) 4350-4357. 10. M.Y. Gong, Y.P. Zhang, C.J. Weschler, Measurement of phthalates in skin wipes: estimating exposure from dermal absorption, Environ. Sci. Technol. 48 (2014) 7428-7435. 11. NIOSH Pocket Guide to Chemical Hazards #0228". National Institute for Occupational Safety and Health (NIOSH). 12. T. M. Trí., K. Kannan, Occurrence of phthalate diesters in particulate and vapor phases in indoor air and implications for human exposure in Albany, New York, USA. Arch. Environ. Contam. Toxicol. 68 (1015) 489-499. 13. Y. Kang, Y.B. Man, K.C. Cheung, M.H. Wong, Risk assessment of human exposure to bioaccessible phthalate esters via indoor dust around the Pearl River Delta, Environ. Sci. Technol. 46 (2012) 8422-8430. 14. Y. Xu, E.A.C. Hubal, P.A. Clausen, J.C. L, Predicting residential exposure to phthalate plasticizer emitted from vinyl flooring: a mechanistic analysis, Environ.Sci. Technol. 43 (2009) 2374-2380. 15. Z. Bu, Y. Zhang, D. Mmereki, W. Yu, B. Li, Indoor phthalate concentration in residential apartments in Chongqing, China: implications for preschool children's exposure and risk assessment, Atmos. Environ. 127 (2016) 34-45.